2005
DOI: 10.1371/journal.pbio.0030123
|View full text |Cite|
|
Sign up to set email alerts
|

Neutralizing Aptamers from Whole-Cell SELEX Inhibit the RET Receptor Tyrosine Kinase

Abstract: Targeting large transmembrane molecules, including receptor tyrosine kinases, is a major pharmacological challenge. Specific oligonucleotide ligands (aptamers) can be generated for a variety of targets through the iterative evolution of a random pool of sequences (SELEX). Nuclease-resistant aptamers that recognize the human receptor tyrosine kinase RET were obtained using RET-expressing cells as targets in a modified SELEX procedure. Remarkably, one of these aptamers blocked RET-dependent intracellular signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
193
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(199 citation statements)
references
References 35 publications
2
193
0
4
Order By: Relevance
“…First, we asked whether RA-dependent Ret activation depends on the presence of an autocrine loop involving ligand-dependent dimerization or, rather, the receptor itself is transactivated by intracellular mechanisms acting on its kinase domain (20). To this end, we used a 2 ¶-fluoro-RNAbased aptamer, named D4, which is a specific inhibitor of dimerization-dependent Ret activation but has no effects on Ret activation induced by mutations of the intracellular tyrosine kinase domain (19). As shown in Fig.…”
Section: Ra-dependent Ret and Extracellular Signal-regulated Kinase Amentioning
confidence: 99%
See 3 more Smart Citations
“…First, we asked whether RA-dependent Ret activation depends on the presence of an autocrine loop involving ligand-dependent dimerization or, rather, the receptor itself is transactivated by intracellular mechanisms acting on its kinase domain (20). To this end, we used a 2 ¶-fluoro-RNAbased aptamer, named D4, which is a specific inhibitor of dimerization-dependent Ret activation but has no effects on Ret activation induced by mutations of the intracellular tyrosine kinase domain (19). As shown in Fig.…”
Section: Ra-dependent Ret and Extracellular Signal-regulated Kinase Amentioning
confidence: 99%
“…All-trans RA (Sigma, St. Louis, MO) was dissolved (10 mmol/L) in DMSO and diluted at the indicated concentration in serum-containing culture medium. Neuroblastoma cells (160,000 per 3.5 cm plate) were treated for 18 hours with 1 mL culture medium containing 10 Amol/L RA plus 50 Ag of the indicated EC-Ret protein or plus 1600 nmol/L of the indicated aptamer after a short denaturation-renaturation step (19). To evaluate the effects of RNA aptamers and EC-Ret proteins on cell differentiation, cells were incubated in 12-well cell plate with 10 Amol/L RA together with 3 Amol/L aptamer or 20 Ag/mL EC-Ret proteins.…”
Section: Cell Culture and Immunoblotting Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…9 Principles of RET inhibition in MTC cells include molecular strategies to interfere with its kinase activity by small molecules [10][11][12] and receptor dimerization using aptamers or soluble RET ectodomain. 13,14 As an alternative, strategies that block RET expression or autophosphorylation are highly promising. We have previously demonstrated that dominant-negative RET proteins that contain mutations in the extreme N-terminal region of the extracellular domain such as HSCR32 or Flag expressed by adenoviral (Ad) vectors inhibit receptor maturation, 15,16 thereby preventing its transport to the membrane.…”
Section: Introductionmentioning
confidence: 99%